Temporal changes in circulating progesterone and pregnancy-associated glycoprotein concentrations in Jakhrana goats with failed pregnancy - SHARMA, N; SINGH, S P; BHARADWAJ, A (The Indian Journal of Animal Sciences, 2020)
This study aimed to evaluate the changes in circulating Progesterone (P4) and Pregnancy-Associated Glycoprotein (PAG) during pregnancy interrupted by abortion and to identify the better predictor of abortion risk in Jakhrana goats. Pluriparous goats (18) were involved in the study. Out of 15 pregnant goats, 3 goats were aborted during the third or fourth months of pregnancy. In the normal pregnancy, mean P4 concentration (13.96±0.27 ng/mL) remained unchanged throughout gestation whereas, the PAG level increased during early pregnancy and reached to the highest level (S-N=2.14±0.40) on day 51 of gestation. In non-pregnant goats, the P4 (0.3±0.03 ng/mL) and PAG (0.06±0.03) were significantly lower compared to the goats with maintained or failed pregnancy. In goats with the failed pregnancy, the PAG level started to decline about 12 days before the drop in P4 concentration (day 33.0±2.1 vs 21.3±3.5, before the occurrence of abortion). The mean PAG level in goats with failed pregnancy (0.33±0.03) was 4.8-folds lower compared to the animals with maintained pregnancy (1.58±0.08). In conclusion, the P4 and PAG concentrations in maternal circulation are changed by the pregnancy status and abortion. Plasma PAG is a more reliable predictor for the high risk of pregnancy failure than the P4 concentration in goats.